Zinc-aspirin preconditioning reduces endothelial damage of arterial grafts in a rodent model of revascularization - Benke, Kálmán; Stengl, Roland; Stark, Klára Aliz; Bai, Yang; Radovits, Tamás; Loganathan, Sivakkanan; Korkmaz-Icöz, Sevil; Csonka, Máté; Karck, Matthias; Szabó, Gábor; Veres, Gábor (Frontiers in Cardiovascular Medicine, 2024)
Introduction Coronary artery bypass grafting (CABG) is the most common cardiac surgical procedure. The prognosis of revascularization via CABG is determined by the patency of the used grafts, for which an intact endothelium is essential. The degree of ischemia-reperfusion injury (IRI), which occurs during the harvest and implantation of the grafts, is an important determinant of graft patency. Preconditioning with aspirin, a nonsteroidal anti-inflammatory drug has been shown to reduce the functional and molecular damage of arterial grafts in a rodent model. Studies have found that the zinc-aspirin complex may be able to exert an even better protective effect in pathological cardiovascular conditions. Thus, our aim was to characterize the protective effect of zinc-aspirin complex on free arterial grafts in a rodent model of revascularization. Methods Donor Lewis rats were treated with either zinc-aspirin, aspirin, or placebo (n = 8) for 5 days, then the aortic arches were harvested and stored in cold preservation solution and implanted heterotopically in the abdominal cavity of the recipient rats, followed by 2 h of reperfusion. There was also a non-ischemia-reperfusion control group (n = 8). Functional measurements using organ bath and histomorphological changes using immunohistochemistry were analyzed. Results The endothelium dependent maximal vasorelaxation was improved (non-transplanted control group: 82% ± 3%, transplanted control group: 14% ± 2%, aspirin group: 31% ± 4%, zinc-aspirin group: 52% ± 4%), the nitro-oxidative stress and cell apoptosis decreased, and significant endothelial protection was shown in the groups preconditioned with aspirin or zinc-aspirin. However, zinc-aspirin proved to be more effective in the reduction of IRI, than aspirin alone. Discussion Preconditioning with zinc-aspirin could be a promising way to protect the function and structural integrity of free arterial grafts, thus improving the outcomes of CABG.